Analysis of Social Capital Effect in the Joint Liability Group on the Performance of Sharia Cooperatives in Indonesia - Nurma Yulita; Amelia Pratiwi (Journal of Economics Research and Social Sciences, 2022)
This investigation aims to analyze the impact of the joint liability model on the sharia cooperatives’ performance in Indonesia. The respondents are several group lending members of sharia cooperatives in Java, the center of sharia cooperatives in Indonesia. This study utilized the purposive sampling method to select samples conducted in April 2021. Data collection was carried out by distributing online and offline questionnaires to several sharia cooperatives utilizing the joint liability model. Data from 98 respondents were further analyzed by PLS-SEM analysis. The results unveiled that joint liability, which was influenced by indicators of trusts, norms, and networks, had a positive and significant effect on sharia cooperatives’ performance as measured by members’ satisfaction and loyalty. Thus, sharia cooperatives can take advantage of and maintain the joint liability model based on trusts, norms, and networks. The rationale is that the joint liability application has followed cooperative principles: the principle of kinship and cooperation. In addition, such a model has proven to increase the loyalty and satisfaction of sharia cooperative members.